Urban Marketing and its Impact over the Touristic Attractiveness of the Cities – A Conceptual Approach - Alexa, Elena (Studies and Scientific Researches. Economics Edition, 2010)
Considering the current issues the urban centers are dealing with, the amplified city competitiveness and the increased demand of qualitative public services, it appears the need to apply new urban management approaches, more oriented toward the market and the current needs of the city. The competitive environment pressure creates the need to pass from an entirely administrative approach to a more managerial one, in all aspects regarding the current problems of the cities. Thus, the urban stakeholders borrow more and more often working methods and techniques specific until now only for the private sector, in order to increase the public service’s performance and to sustainable develop their community. Urban marketing came as a natural response to the cities needs to bring added value to their urban management strategies. The final objective is to increase the cities attractiveness for different target groups: starting with the current and future inhabitants, continuing with tourists and finishing with potential investors, which by relocating their business, could become a part of the faster and more sustainable urban development.